Harnessing exosomes as a platform for drug delivery in breast cancer: A systematic review for in vivo and in vitro studies - Abdulwahab Teflischi Gharavi; Saeed Irian; Azadeh Niknejad; Keykavous Parang; Mona Salimi (Molecular Therapy: Oncology)
Breast cancer remains a significant global health concern, emphasizing the critical need for effective treatment strategies, especially targeted therapies. This systematic review summarizes the findings from in vitro and in vivo studies regarding the therapeutic potential of exosomes as drug delivery platforms in the field of breast cancer treatment. A comprehensive search was conducted across bibliographic datasets, including Web of Science, PubMed, and Scopus, using relevant queries from several related published articles and the Medical Subject Headings Database. Then, all morphological, biomechanical, histopathological, and cellular-molecular outcomes were systematically collected. A total of 30 studies were identified based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. These studies underwent assessment using the Systematic Review Centre for Laboratory Animal Experimentation risk of bias assessment tool. The results indicate that exosomes exhibit promise as effective drug delivery platforms, capable of hindering cancer cell viability, proliferation, migration, and angiogenesis. However, a comprehensive assessment is challenging due to some studies deviating from guidelines and having incomplete methodology. Addressing these, future studies should detail methodologies, optimize dosing, and enhance exosome production. Standardization in reporting, consistent protocols, and exploration of alternative sources are crucial.